GANTI KERUGIAN OBJEK PENGADAAN TANAH WARGA SUMBERJAYA UNTUK PEMBANGUNAN TOL CIBITUNG CILINCING - Putri Viryal Dewi; Intan Nevia Cahyana (Fakultas Hukum Universitas Trisakti, 2022)
In the land acquisition process, compensation is an appropriate and reasonable recompense to the rightful party. However, it was discovered during the implementation phase that various residents had disputed land ownership, making it unclear which party was entitled to pay. The issue at hand concerns whether the payment of compensation for land acquisition objects for Sumberjaya residents in the Bekasi district complies with Law No. 2 of 2012, as well as what barriers exist to compensation and how the land acquisition committee is attempting to resolve them. The research is normative legal research, and because it is descriptive analytical in character, primary and secondary data were used. The study used deductive reasoning to conduct its qualitative investigation. According to research, Law No. 2 of 2012 requires compensation for land acquisition items, but there were issues with its implementation. The supply of compensation for land acquisition objects, namely land conflicts, is stated to be in compliance with Law No. 2 of 2012, and despite the challenges faced, settlement efforts are being undertaken by the land acquisition committee.